Silver nanoparticles of different sizes induce a mixed type of programmed cell death in human pancreatic ductal adenocarcinoma - Zielinska, Ewelina (Oncotarget, 2017)
Pancreatic ductal adenocarcinoma, with the high resistance to chemotherapeutic agents, remains the fourth leading cause of cancer-death in the world. Due to the wide range of biological activity and unique properties, silver nanoparticles (AgNPs) are indicated as agents with potential to overcome barriers involved in chemotherapy failure. Therefore, in our study we decided to assess the ability of AgNPs to kill pancreatic cancer cells, and then to identify the molecular mechanism underlying this effect. Moreover, we evaluated the cytotoxicity of AgNPs against non-tumor cell of the same tissue (hTERT-HPNE cells) for comparison. Our results indicated that AgNPs with size of 2.6 and 18 nm decreased viability, proliferation and caused death of pancreatic cancer cells in a size- and concentration-dependent manner. Ultrastructural analysis identified that cellular uptake of AgNPs resulted in apoptosis, autophagy, necroptosis and mitotic catastrophe. These alterations were associated with increased pro-apoptotic protein Bax and decreased level of anti-apoptotic protein Bcl-2. Moreover, AgNPs significantly elevated the level of tumor suppressor p53 protein as well as necroptosis- and autophagy-related proteins: RIP-1, RIP-3, MLKL and LC3-II, respectively. In addition, we found that PANC-1 cells were more vulnerable to AgNPs-induced cytotoxicity compared to pancreatic non-tumor cells. In conclusion, AgNPs by inducing mixed type of programmed cell death in PANC-1 cells, could provide a new therapeutic strategy to overcome chemoresistance in one of the deadliest human cancer.